EFEKTIVITAS PEMBELAJARAN DARING DALAM PEMBELAJARAN FIKIH DI KELAS III MIN I PASURUAN DESA GUNUNG GANGSIR KECAMATAN BEJI KABUPATEN PASURUAN - Nanang Rokman Saleh Saleh; Muhammad Syaikhon; Machmudah Machmudah (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2022)
The Covid-19 pandemic which became a global pandemic in the early March 2020 forced the world to lock down as an effort to prevent the spread of the virus. In Indonesia, PSBB is applied for all activities outside home until the pandemic subsides. Specifically, related to education, the government issues policies so that learning is carried out online. MIN 1 Pasuruan is one of the educational institutions under the auspices of the Ministry of Religion that implements online learning. Online learning is a new thing, which creates problems and obstacles for parents, students, teachers and schools, so they are interested to be researched about its effectiveness in learning. This study aims to describe the effectiveness of online learning in Fiqh learning in Class III A MIN 1 Pasuruan, Gunung Gangsir Village, Beji District, Pasuruan Regency. The data sources in this study consisted of primary sources in the form of school principal data, while secondary data in the form of results from observations, interviews, and documentation activities at MIN 1 Pasuruan. Data collection techniques in this study used the methods of observation, interviews, and documentation. The data analysis technique in this study used the Miles and Huberman analysis method so that it could be seen the effectiveness of online learning in Fiqh learning in Class III A MIN 1 Pasuruan. The results showed that online learning for Fiqh learning in Class III/A MIN 1 Pasuruan, Gunung Gangsir Village, Beji District, Pasuruan Regency was less effective.